Potential Applications of Fluorescence-Activated Cell Sorting (FACS) and Droplet-Based Microfluidics in Promoting the Discovery of Specific Antibodies for Characterizations of Fish Immune Cells - Fei, Chenjie; Nie, Li; Zhang, Jianhua; Chen, Jiong (Frontiers in Immunology, 2021)
Akin to their mammalian counterparts, teleost fish possess a complex assortment of highly specialized immune cells that are capable of unleashing potent innate immune responses to eradicate or mitigate incoming pathogens, and also differentiate into memory lymphocytes to provide long-term protection. Investigations into specific roles and functions of fish immune cells depend on the precise separation of each cell type. Commonly used techniques, for example, density gradient centrifugation, rely on immune cells to have differing sizes or densities and thus fail to separate between similar cell types (e.g. T and B lymphocytes). Furthermore, a continuously growing database of teleost genomic information has revealed an inventory of cellular markers, indicating the possible presence of immune cell subsets in teleost fish. This further complicates the interpretation of results if subsets of immune cells are not properly separated. Consequently, monoclonal antibodies (mAbs) against specific cellular markers are required to precisely identify and separate novel subsets of immune cells in fish. In the field of fish immunology, mAbs are largely generated using the hybridoma technology, resulting in the development of mAbs against specific cellular markers in different fish species. Nevertheless, this technology suffers from being labour-intensive, time-consuming and most importantly, the inevitable loss of diversities of antibodies during the fusion of antibody-expressing B lymphocytes and myeloma cells. In light of this, the focus of this review is to discuss the potential applications of fluorescence-activated cell sorting and droplet-based microfluidics, two emerging technologies capable of screening and identifying antigen-specific B lymphocytes in a high-throughput manner, in the field of fish immunology. Our main goal is to encourage the incorporation of alternative technologies into our field to promote the production of specific antibodies in a high-throughput and cost-effective way, which could better allow for the precise separation of fish immune cells and also facilitate the identification of novel immune cell subsets in teleost fish.